Self-Acceptance of Saye’s (Tajen Judge) Children in Bali - Ardhana, Dewa Ayu Venny; Susana, Tjipto; Ninin, Retno Hanggarani (Jurnal Psikologi, 2024)
Self-acceptance plays a crucial role in mental health and emotional well-being. In Balinese society, children living with a parent who works as a saye and is involved in gambling struggle to accept themselves. Therefore, it is urgent to understand or study the experiences of saye’s children and their self-acceptance. This study used a phenomenological qualitative approach, and the data were analyzed using the thematic analysis method. The data were gathered through semi-structured and narrative interviews. There were three participants aged 18-25 years living with a parent who works as a saye (tajen judge). The results of this study showed that: 1) The children of the saye have unpleasant experiences related to stigma, stereotypes, verbal bullying, and their fathers’ anger when losing a gamble; 2) The children go through stages of self-acceptance, such as denial and rationalization, becoming involved in the gambling activity, finding meaning, and achieving self-acceptance; and 3) Factors that contribute to the children’s self-acceptance include the socio-cultural environment, positive support, and democratic parenting. To increase the self-acceptance of saye’s children, families should provide a safe environment for children, and society should not stigmatize saye’s families. The results of this research cannot simply be applied to other regions because Gianyar Regency carries out tajen activities more frequently compared to other locations. Future research needs to explore other areas in Bali.